An Experimental Study on the Reduction of Temperature of Cool Pavement Specimens - Shambhavi S., Dr. R. M. Mahalingegowda, Dr. K. C. Manjunath (International Journal of Advanced Science and Technology, 2020)
Cool pavement is a pavement that reduces pavement temperature by increasing pavement reflectivity or controlling temperature, thereby reducing urban heat island effects.The study was conducted in PES College of Engineering, Mandya for conventional pavement specimens & cool pavement specimens to determine the temperature variations & strength comparison between them. The comparisons are as follows: Under the tree shade: In CCP-CCP 1L there is reduction of 1°C, in CCP – CCP 2L reduction of 1.2°C, in CCP-CCP porous reduction of 2.5°C, in bitumen-bitumen 1L reduction of 2.9°C. Direct exposure to sun: In CCP-CCP 1L there is reduction of 1.9°C, in CCP – CCP 2L reduction of 3.2°C, in CCP-CCP porous rise of 0.1°C, in CCP-CCP porous 1L reduction of 3.0°C, in bitumen-bitumen 1L reduction of 3.9°C, in bitumen-bitumen 2L reduction of 5.0°C.The compressive strength of porous concrete is 73.96 % lesser than that of conventional concrete. The split tensile strength of porous concrete is 50.46 % lesser than that of strength of conventional concrete. The flexural strength of porous concrete is 48.99% lesser than that of strength of conventional concrete.